A Virginia cavalier - Seawell, Molly Elliot, 1860-1916; Yohn, F. C. (Frederick Coffay), 1875-1933 (Salt Lake City, UT : Project Gutenberg, 2023)
"A Virginia Cavalier" by Molly Elliot Seawell is a historical novel written in the late 19th century. The narrative centers around a young George Washington as he navigates his formative years and the early days of his life in Virginia, framed against the backdrop of the lush and serene midland countryside. It explores themes of character, honor, and the influences that shape great leaders. At the start of the novel, the idyllic setting of Virginia in late October 1746 is vividly described, invoking a sense of peace and beauty that envelops young George Washington as he hunts in the woods. The chapter introduces readers to George's natural skill as a woodsman and his admiration for a passing nobleman, the Earl of Fairfax, hinting at the significance of this encounter in shaping his future. From conversations about family and expectations to George's growing responsibilities in his mother's household, the opening lays groundwork for a character driven by virtue, duty, and ambition$1 (Bthe hallmarks of the leader he is destined to become. (This is an automatically generated summary.)s
Release date is 2023-09-17
D A Alexander, David E. Brown, with special thanks to Abbey Maynard, Courtesy Charles Deering McCormick Library of Special Collections and University Archives, Northwestern University Libraries for providing the missing illustrations, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Washington, George, 1732-1799 -- Juvenile fiction